2020
DOI: 10.1002/essoar.10504510.1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Electron Bulk Heating at Saturn's Magnetopause

Abstract: The magnetopause (MP) is the natural boundary of a planetary magnetosphere. It is formed by the interaction between the solar wind and planetary magnetosphere. At Saturn, it separates the magnetospheric magnetic field and plasma (mainly from the moon Enceladus) from the interplanetary magnetic field (IMF) and solar wind plasma that has to flow around the magnetospheric obstacle (Baines et al., 2018). Cassini observations of magnetic field and plasma have also revealed that the disk-like magnetosphere imposes a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…They showed that the weaker the B-gradient, the higher the energy of electrons is required to escape into the magnetosheath: E.g., for a magnetic field gradient scale length of ~17 R E along the magnetopause, the minimum kinetic energy for loss is ~3 MeV. The large variety of MP crossings is likely due to the different plasma processes and evolving structures which may occur at the MP boundary such as electron heating associated with magnetic reconnection (McAndrews et al, 2008;Cheng et al, 2021), Kelvin-Helmholtz vortices, (Masters et al, 2010), plasma depletion layers (Masters et al, 2014) and low-latitude boundary layers (Masters et al, 2011).…”
Section: Bs and Mp Crossing Featuresmentioning
confidence: 99%
“…They showed that the weaker the B-gradient, the higher the energy of electrons is required to escape into the magnetosheath: E.g., for a magnetic field gradient scale length of ~17 R E along the magnetopause, the minimum kinetic energy for loss is ~3 MeV. The large variety of MP crossings is likely due to the different plasma processes and evolving structures which may occur at the MP boundary such as electron heating associated with magnetic reconnection (McAndrews et al, 2008;Cheng et al, 2021), Kelvin-Helmholtz vortices, (Masters et al, 2010), plasma depletion layers (Masters et al, 2014) and low-latitude boundary layers (Masters et al, 2011).…”
Section: Bs and Mp Crossing Featuresmentioning
confidence: 99%